Digestive Symptoms in COVID-19 Patients With Mild Disease Severity: Clinical Presentation, Stool Viral RNA Testing, and Outcomes - Han, Chaoqun; Duan, Caihan; Zhang, Shengyan; Spiegel, Brennan; Shi, Huiying; Wang, Weijun; Zhang, Lei; Lin, Rong; Liu, Jun; Ding, Zhen; Hou, Xiaohua (The American journal of gastroenterology, 2020)
Coronavirus disease 2019 (COVID-19) most commonly presents with respiratory symptoms, including cough, shortness of breath, and sore throat. However, digestive symptoms also occur in patients with COVID-19 and are often described in outpatients with less severe disease. In this study, we sought to describe the clinical characteristics of COVID-19 patients with digestive symptoms and mild disease severity. We identified COVID-19 patients with mild disease and one or more digestive symptoms (diarrhea, nausea, and vomiting), with or without respiratory symptoms, and compared them with a group presenting solely with respiratory symptoms. We followed up patients clinically until they tested negative for COVID-19 on at least 2 sequential respiratory tract specimens collected ≥24 hours apart. We then compared the clinical features between those with digestive symptoms and those with respiratory symptoms. There were 206 patients with low severity COVID-19, including 48 presenting with a digestive symptom alone, 69 with both digestive and respiratory symptoms, and 89 with respiratory symptoms alone. Between the 2 groups with digestive symptoms, 67 presented with diarrhea, of whom 19.4% experienced diarrhea as the first symptom in their illness course. The diarrhea lasted from 1 to 14 days, with an average duration of 5.4 ± 3.1 days and a frequency of 4.3 ± 2.2 bowel movements per day. Concurrent fever was found in 62.4% of patients with a digestive symptom. Patients with digestive symptoms presented for care later than those with respiratory symptoms (16.0 ± 7.7 vs 11.6 ± 5.1 days, P < 0.001). Nevertheless, patients with digestive symptoms had a longer duration between symptom onset and viral clearance (P < 0.001) and were more likely to be fecal virus positive (73.3% vs 14.3%, P = 0.033) than those with respiratory symptoms. We describe a unique subgroup of COVID-19 patients with mild disease severity marked by the presence of digestive symptoms. These patients are more likely to test positive for viral RNA in stool, to have a longer delay before viral clearance, and to experience delayed diagnosis compared with patients with only respiratory symptoms.